Struktur Kaidah Fiqhiyyah: Fondasi Universal Dalam Penetapan Hukum Islam - R, Rahmatullah; Musyahid, Ahmad (Media Hukum Indonesia (MHI), 2025)
Fiqhiyyah rules are fundamental elements in the Islamic legal system that function as universal principles in determining laws based on sharia values. This article aims to systematically examine the structure of fiqhiyyah rules, starting from their constituent elements, their classification, to their function in responding to contemporary legal problems. Using a qualitative normative and historical-analytical approach, this study examines relevant classical and contemporary literature, and relates it to the maqasid al-syari'ah approach. The results of the study indicate that the structure of fiqhiyyah rules consists of general principles that are cross-disciplinary, systemically coherent, and able to interact with the modern social context without losing their normative basis. In addition, fiqhiyyah rules have been proven to have a strategic function in the methodology of ijtihad and the reconstruction of Islamic law, and have made a significant contribution to the integration between nash, maqasid, and reality. This study emphasizes that strengthening structural understanding of fiqhiyyah rules is very important in building a responsive, rational, and just Islamic legal system.